Optimization of Electronic Domain‐Wall Properties by Aliovalent Cation Substitution. (8th December 2015) - Schaab, Jakob; Cano, Andres; Lilienblum, Martin; Yan, Zewu; Bourret, Edith; Ramesh, Ramamoorthy; Fiebig, Manfred; Meier, Dennis
Abstract : Electronic domain‐wall conductance is controlled by chemical aliovalent doping in the p‐type semiconductor Er1‐ x Ca x MnO3 . Coexisting bound (top panel) and mobile (lower panel) charges at the walls are analyzed using electrostatic force microscopy. Emergent doping‐related variations are quantified by local transport measurements and explained based on phenomenological theories.